Influence of the heterogeneous reaction HCl + HOCl on an ozone hole model with hydrocarbon additions - Elliott, Scott; Cicerone, Ralph J; Turco, Richard P; Drdla, Katja; Tabazadeh, Azadeh (Journal of Geophysical Research: Atmospheres, 1994)
Injection of ethane or propane has been suggested as a means for reducing ozone loss within the Antarctic vortex because alkanes can convert active chlorine radicals into hydrochloric acid. In kinetic models of vortex chemistry including as heterogeneous processes only the hydrolysis and HCl reactions of ClONO2 and N2O5, parts per billion by volume levels of the light alkanes counteract ozone depletion by sequestering chlorine atoms. Introduction of the surface reaction of HCl with HOCl causes ethane to deepen baseline ozone holes and generally works to impede any mitigation by hydrocarbons. The increased depletion occurs because HCl + HOCl can be driven by HOx radicals released during organic oxidation. -from Authors